2017
DOI: 10.1038/hr.2017.75
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity and hypertension: an updated comprehensive overview on vicious twins

Abstract: Obesity is a growing global health concern, with a rapid increase being observed in morbid obesity. Obesity is associated with an increased cardiovascular risk and earlier onset of cardiovascular morbidity. The growing obesity epidemic is a major source of unsustainable health costs and morbidity and mortality because of hypertension, type 2 diabetes mellitus, dyslipidemia, certain cancers and major cardiovascular diseases. Similar to obesity, hypertension is a key unfavorable health metric that has disastrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
144
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(162 citation statements)
references
References 263 publications
11
144
0
7
Order By: Relevance
“…This finding is not surprising, given that obesity is a leading risk factor for both diabetes and hypertension. The global prevalence of obesity has nearly doubled in the past three decades; in the USA, 36% of adults have a BMI ≥30, it is estimated nearly 90% of diabetes is attributable to excess weight and excess weight accounts for 65–75% of the risk for hypertension . This vicious synergistic combination of obesity, diabetes, and hypertension also increases the risk for cardiovascular disease and chronic kidney disease .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not surprising, given that obesity is a leading risk factor for both diabetes and hypertension. The global prevalence of obesity has nearly doubled in the past three decades; in the USA, 36% of adults have a BMI ≥30, it is estimated nearly 90% of diabetes is attributable to excess weight and excess weight accounts for 65–75% of the risk for hypertension . This vicious synergistic combination of obesity, diabetes, and hypertension also increases the risk for cardiovascular disease and chronic kidney disease .…”
Section: Discussionmentioning
confidence: 99%
“…A túlsúly és az elhízás nem pusztán a zsírszövet felszaporodását jelenti, hanem elindít egy olyan összetett anyagcserekaszkádot, mely végül a vérnyomás emelkedéséhez vezet [33]. Ez a folyamat fokozza a szív-és érrendszeri betegségek kialakulásának kockázatát a betegnél.…”
Section: Eredeti Közleményunclassified
“…Az emelkedett LDL-koleszterin-szint krónikus gyulladást képes indukálni, míg az inzulinrezisztencia gátolhatja a zsírszövet lipolízisét, ami emeli a szabad zsírsavak (free fatty acids, FFA) szintjét a szérumban [38]. Az emelkedett szabadzsírsav-szint fokozza az alfa-adrenerg-rendszer hatását, növelve ezzel az artériás tónust [33]. A fentiek alapján megállapíthatjuk, hogy az elhízáshoz társuló vérnyomás-emelkedés kialakulása öszszetett folyamat, melynek lényege a felszaporodott zsírsejtek anyagcserehatásai által aktivált szimpatikus idegrendszer regulációs zavara.…”
Section: Táblázatunclassified
“…Studies propose that approximately 70% of hypertension risk can be attributed to the presence of excessive body weight [63][64][65]. Epidemiological studies showed that adiposity and hypertension are precursor factors for CVD development [66].…”
Section: Blood Pressure (Sbp and Dbp)mentioning
confidence: 99%